Acute Lower-Extremity Posterior Compartment Syndrome: A Rare Complication of Apixaban Use - Jennifer Adams; Jose H. Ramos; Shyama Appareddy; Hoang Anh Thi Nguyen; Gustavo Garcia (Annals of Internal Medicine: Clinical Cases)
Apixaban is an oral anticoagulant that directly inhibits factor Xa and is indicated for the prophylaxis and treatment of deep venous thrombosis and stroke prevention in nonvalvular atrial fibrillation. Acute lower-extremity posterior compartment syndrome is a rare complication of apixaban use. We present a 78-year-old man with significant medical morbidities taking apixaban for atrial fibrillation presenting with posttraumatic extensive hemorrhagic bullae on the left proximal pretibial region secondary to anticoagulation. We recommend that clinicians develop awareness of the potential for serious bleeding complications of anticoagulants and devise strategies to identify the need for early recognition and prompt management.